2000
DOI: 10.1039/a906090a
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of cyclic octapeptides and the influence of heterocyclic ring constraints upon calcium binding †

Abstract: A comparison is made between the structures and calcium binding properties of four cyclic octapeptides that differ in the number of heterocyclic thiazole and oxazoline ring constraints. The conformations of the naturally occurring cyclic octapeptides ascidiacyclamide 1 and patellamide D 2, which each contain two oxazoline and two thiazole rings, are compared by 1 H NMR spectroscopy with the analogues cyclo(Thr--Val(Thz)-Ile) 2 3 with just two thiazoles, and cyclo(Thr--Val-αAbu-Ile) 2 4, with no 5-membered ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Initial quantitative investigations of the interactions of metal ions with a range of patellamides were undertaken using NMR, EPR, UV-vis-NIR and circular dichroism (CD) spectroscopy. For many reasons Cu II usually was the metal ion of choice, driven to some extent by the spectroscopic advantages of the d 9 electronic configuration but also by the biologi- 76 The potassium complex of a partially hydrolyzed ascidiacyclamide was structurally characterized (Fig. 7).…”
Section: Lissoclinum Bistratum Derived Peptidesmentioning
confidence: 99%
“…Initial quantitative investigations of the interactions of metal ions with a range of patellamides were undertaken using NMR, EPR, UV-vis-NIR and circular dichroism (CD) spectroscopy. For many reasons Cu II usually was the metal ion of choice, driven to some extent by the spectroscopic advantages of the d 9 electronic configuration but also by the biologi- 76 The potassium complex of a partially hydrolyzed ascidiacyclamide was structurally characterized (Fig. 7).…”
Section: Lissoclinum Bistratum Derived Peptidesmentioning
confidence: 99%
“…The recognition of the potential role of cyclic peptides of marine origin as ionophores in biological systems has prompted a number of studies of the complexation reactions of these peptides with the transition and non-transition elements [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Studies of the metal binding properties of these molecules have been suggested to have important implications regarding the biological activity of these compounds in vivo, [13,17] and one study has suggested that copper(II) is the biologically relevant metal for the patellamides, one class of these peptides [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our interest has been in the chemistry of these molecules with zinc(II), calcium(II) and copper(II) [3,4,[7][8][9][10]. Previous spectroscopic investigations (electronic absorption, circular dichroism (CD), electron paramagnetic resonance (EPR) spectroscopy and mass spectrometry) of the complexation of patellamide D by copper(II) in methanol identified multiple mono-and bi-nuclear copper(II) complexes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive complexation studies with patellamide-type ligands [14,18,21,28] have revealed a number of mono-and dinuclear species in solution. An interesting feature is that, quite generally, two types of dinuclear complexes are observed in slow equilibria (usually a blue and a purple compound), and these were assigned to the slow formation of carbonato-bridged dicopper(ii) compounds, [13] to variations in the deprotonation pattern of the ligands and corresponding changes in the donor sets or to partial deprotonation of the aqua coligands.…”
Section: Introductionmentioning
confidence: 99%